Panax notoginseng polysaccharide increases stress resistance and extends lifespan in Caenorhabditis elegans - Feng, Shiling; Cheng, Haoran; Xu, Zhou; Yuan, Ming; Huang, Yan; Liao, Jinqiu; Yang, Ruiwu; Zhou, Lijun; Ding, Chunbang (Journal of functional foods, 2018)
Panax notoginseng is Traditional Chinese medicine and also a China Food and Drug Administration (CFDA) approved food additive. In present study, we used Caenorhabditis elegans model to illustrate stress resistance and lifespan extension effect of a polysaccharide fraction form P. notoginseng (MRP5). Our data showed that MRP5 could significantly increase survival rate and markedly decreased ROS level of C. elegans under oxidative stress. Moreover, MRP5 could reduce the level of carbonyl protein and malondialdehyde of BA17 strain and extend lifespan of wild-type worms. The mechanism study revealed that MRP5 was able to promote the nuclear localization of DAF-16 resulting in the activation of antioxidant enzymatic systems. We also observed that MRP5 increased lifespan of daf-16 loss-of function mutant, suggesting MRP5-prolonged lifespan partially required daf-16 gene. Overall, our results illustrated the potential utilization of MRP5 as a functional food ingredient to delay aging.
Gesehen am 07.05.2020